Comparing groups versus individuals in decision making: a systematic review protocol. Issue 1 (December 2016) - Mukherjee, Nibedita; Dicks, Lynn; Shackelford, Gorm; Vira, Bhaskar; Sutherland, William
Abstract Background Biodiversity management requires effective decision making at various stages. However decision making in the real world is complex, driven by multiple factors and involves a range of stakeholders. Understanding the factors that influence decision making is crucial to addressing the conflicts that arise in conservation. Decisions can be made either by individuals or by groups. This precise context has been studied extensively for several decades by behavioural economists, social psychologists and intelligence analysts. The observations from these disciplines can offer useful insights for biodiversity conservation. A systematic review on group versus individual decision making is currently lacking. This systematic review would enable us to synthesize the key insights from these disciplines for a range of scenarios useful for conservation. Methods The review will document studies that have investigated differences between group and individual decision making. The focus will be on empirical studies; the comparators in this case are decisions made by individuals while the intervention is group decision making. Outcomes include level of bias in decision outcomes or group performance. The search terms will include various combinations of the words "group", "individual" and "decision-making". The searches will be conducted in major publication databases, google scholar and specialist databases. Articles will be screened at the title and abstract and full text level by two reviewers. After checking for internal validity, the articles will be synthesized into subsets of decision contexts in which decision making by groups and individuals have been compared. The review process, all extracted data, original studies identified in the systematic review process and inclusion and exclusion decisions will be freely available as Additional file 1 in the final review.